Response to 'Letter to the editor' by Wienholtz et al. entitled 'The many faces of rosacea: liberal diagnostic criteria have ramifications on disease prevalence and accuracy'. (27th June 2019) - Tizek, L.; Schielein, M.C.; Seifert, F.; Biedermann, T.; Böhner, A.; Zink, A.
Abstract : Linked article: N. Wienholtz J Eur Acad Dermatol Venereol 2019; 33 : e426–e427. https://doi.org/10.1111/jdv.15748 .